2000
DOI: 10.1152/jappl.2000.88.4.1390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of systemic arterial blood pressure on the contractile force of a human hand muscle

Abstract: The effect of physiological changes in systemic blood pressure on the force output of working abductor pollicis (AP) muscle was studied in six normal subjects. Supramaximal tetanic stimulation at the ulnar nerve produced repeated isometric contractions at 1-s intervals. Force output declined gradually with time. During the train of contractions, subjects voluntarily contracted the knee extensors for 1 min; this raised systemic blood pressure by 29%. Force output from AP rose in parallel with blood pressure so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…Conversely, minimal flow recovery was observed when local forearm perfusion pressure was acutely reduced via positional changes (i.e., forearm above heart level) (498). A lack of flow restoration with positional perfusion lowering is further supported by the idea that muscle force production is reduced and fatigue can be increased by reductions in perfusion pressure (517,518). Taken together, the magnitude of flow restoration or compensation and mechanisms involved appear to be dependent on the experimental approach used to induce hypoperfusion in contracting skeletal muscle.…”
Section: O Blood-borne Vasodilator Substancesmentioning
confidence: 98%
“…Conversely, minimal flow recovery was observed when local forearm perfusion pressure was acutely reduced via positional changes (i.e., forearm above heart level) (498). A lack of flow restoration with positional perfusion lowering is further supported by the idea that muscle force production is reduced and fatigue can be increased by reductions in perfusion pressure (517,518). Taken together, the magnitude of flow restoration or compensation and mechanisms involved appear to be dependent on the experimental approach used to induce hypoperfusion in contracting skeletal muscle.…”
Section: O Blood-borne Vasodilator Substancesmentioning
confidence: 98%
“…The different rate of increase in mean arterial pressure when the upper arm was vertical suggests that the muscle mass involved differed for the two tasks (66,69). Indeed, the EMG activity for the anterior deltoid muscle increased more rapidly during the position task when the upper arm was vertical (33), whereas the rate of increase was similar for the two tasks when the upper arm was horizontal (62).…”
Section: Limb Posturementioning
confidence: 99%
“…In contrast, the response of vasoregulatory mechanisms to altered perfusion pressure-induced changes in oxygen delivery may be less effective (31,36,37). Wright et al have demonstrated that force output of electrically stimulated contracting human hand muscle is sensitive to changes in perfusion pressure evoked either by altering hand position relative to heart level (36) or via metaboreflex-induced elevation in systemic arterial blood pressure (37).…”
mentioning
confidence: 99%
“…In contrast, the response of vasoregulatory mechanisms to altered perfusion pressure-induced changes in oxygen delivery may be less effective (31,36,37). Wright et al have demonstrated that force output of electrically stimulated contracting human hand muscle is sensitive to changes in perfusion pressure evoked either by altering hand position relative to heart level (36) or via metaboreflex-induced elevation in systemic arterial blood pressure (37). Similar alterations in electrically stimulated canine muscle force output when oxygen delivery is systematically altered (9) would suggest that in the experiments of Wright et al, exercising muscle blood flow was altered with perfusion pressure and vasoregulatory mechanisms did not fully compensate.…”
mentioning
confidence: 99%